Gaussian Integer Solutions Of The Diophantine Equation + = For ≠ - Shahrina Ismail; Kamel Ariffin Mohd Atan; Diego Sejas-Viscarra; Kai Siong Yow (College of Science for Women/ University of Baghda, 2024)
Indexed by Scopus